The precision of the migration image of the depth section on the seismometry observations on northwestern Black Sea shelf - О.О. Верпаховська; В.П. Коболев; В.М. Пилипенко (Геофизический журнал, 2023)
For many years, the Institute of geophysics has been developing original versions of the finite-difference migration and wavefield modeling techniques for a valid reproduction of the geological cross-section. The modeling provides a practical test of the accuracy of the reproduction of various geological structure features on a migration result and a way to define, in the observed field, the waves which can be used to produce a migration image of the geologic environment efficiently.